Education For All in Nigeria, West Africa: The Journey So Far - Sa'ad, Tajudden; Dahiru, Abba Halilu (NIU Journal of Social Sciences, 2018)
Twenty-two years after the World Conference on Education for All (EFA) in Jomtien, where countries reaffirmed commitment to meet basic learning needs of all children, youths, and adults. Specific goals, in the light of which countries agreed to establish national targets, included universal access to and completion of basic education by the year 2000 and the reduction of adult illiteracy, with specific emphasis on eliminating gender disparities in educational opportunities. The World Education Forum in Dakar 2000 provided the opportunity to take stock of the achievements, the lessons and the failures of the EFA goals. The most disappointing lesson is that the objectives from Jomtien have not been achieved. Yet for 125 million children the right to education is violated every day, leaving them trapped in poverty. For millions more children, lack of teachers, classrooms, and books means their education is cut short and little is learnt. According to International Consultation of NGOs (2000), girls account for two-thirds of the children out of school. One in three adults in the developing world - 880 million people - is still illiterate.